Elementary School Teachers’ Pedagogical Practices in Deep Learning Oriented Toward Critical and Creative Thinking - Juriana Juriana; Agung Hartoyo; Asriah Nurdini Mardiyyaningsih; Juriana; Agung Hartoyo (Universitas Negeri Malang, 2026)
The rapid transformation of twenty-first-century education requires learning processes that foster students’ higher-order thinking skills, particularly critical and creative thinking. However, mathematics instruction in elementary schools often remains focused on procedural knowledge and answer-oriented learning. This study aims to explore teachers’ pedagogical practices in implementing deep learning-oriented instruction in place value learning and to examine their contribution to the development of students’ critical and creative thinking skills. A qualitative case study design was conducted in an elementary school involving a Grade V teacher, students, and school stakeholders. Data were collected through classroom observations, semi-structured interviews, and document analysis. The data were analyzed using an interactive qualitative approach consisting of coding, categorization, and interpretation. The findings reveal that deep learning principles were partially integrated into classroom practice through contextual learning activities, collaborative tasks, the use of concrete learning media, questioning strategies, and reflective activities. Students demonstrated emerging abilities to explain their reasoning, compare numerical values, and connect mathematical concepts to real-life situations. Nevertheless, the development of critical and creative thinking skills remained uneven and at an early stage. Furthermore, assessment practices were still predominantly focused on procedural accuracy, which limited opportunities for students to engage in deeper reasoning and problem-solving processes. In conclusion, deep learning-oriented instruction shows considerable potential for enhancing students’ higher-order thinking skills in mathematics learning. However, its effectiveness depends on stronger alignment among lesson planning, instructional implementation, and assessment practices to support meaningful and sustained learning outcomes.